Análise dos casos de hanseníase na região metropolitana de Aracaju no período de 2001 a 2013 utilizando os dados do SINAN, Sergipe, Brasil - Menezes, Jurema Cristina Machado de (2015)
Leprosy is a chronic infectious disease caused by the bacillus Mycobacterium leprae, which is transmitted from person to person by continuous contact with infectious patients without treatment. In Brazil, due to its endemicity is an important public health problem. This study aimed to analyze and map epidemiological data of leprosy in the metropolitan area of Aracaju, Sergipe. It performed a longitudinal retrospective study based on secondary data from the Notifiable Diseases Information System (SINAN) aiming to achieve the spatial distribution, temporal analysis and describe the epidemiological profile of leprosy in the metropolitan area of Aracaju, Sergipe, Brazil, in the period from 2001 to 2013. Information regarding the patients were collected in the SINAN database provided by the State Health Department of Sergipe. Interest surveyed variables were: municipality of residence, number of cases diagnosed per year, age, education, race, operational classification, clinical form, disability grade, form of entry into the reporting system. The temporal analysis of leprosy in the metropolitan area of Aracaju identified a declining trend in the disease, when studying the municipalities together. The high number of cases with indeterminate clinical form shows that there is a high bacterial load circulating in the community, the statement of Kernel density showed that the hottest areas are concentrated in the center of Aracaju, and will spread by other municipalities in Region Metropolitan Aracaju. These results show the regions where the risk of infection by the bacillus Mycobacterium leprae can occur, showing that leprosy transmission is occurring in the study area, generating new cases. It is of utmost importance that the research activities and leprosy control are maintained and developed for the purpose of disposal and effective control of this disease.